Gender Perspective in Motivation to Study Medicine and Option of Future Practice; A Cross-Sectional Survey in Two Medical Colleges of Karachi, Pakistan - Sheena Mustafa, Mahwish Shah, Saba Khan, Sadia Rashid, Najma Bano Shaikh, Sarosh-Ul Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To access the reasons that are the driving force for joining the medical field, whether willingly, by parents' wish, or because clinicians are the role models and the career choice of the medical students, Methods: This cross-sectional questionnaire-based study was conducted at Jinnah Medical & Dental College and Dow University, Karachi, from May 2018 to November 2018. All the undergraduate medical (MBBS) students were randomly selected, choosing 40 students from each class in an equal number according to gender (20 female students and 20 male students), first to final years from both of the colleges. Consent to participation was obtained verbally from all of the individuals. A questioner was structured regarding demographic information along with reasons for choosing the medical profession and specialty choice for a future career. All the information was collected by using the questioner based self-made study proforma. Results: A total of 400 students were studied. The majority of the students 59.6% were aged 20–22 years, while 40.5% were 23–26 years old. According to the reasons for choosing the medical profession, 37.0% were due to personal interest and parental wishes, 6.8% said their parents are doctors and they are following them, 28.5% students choose the medical profession to serve humanity, 10.5% chose it for high income, 10.3% followed it as a role model, and 7.0% had multiple other reasons. Most common career choices were 26.5% medicine, 30.0% surgery, 5.3% gynaecology, and 7.5% public health, while 8.0% of students still had not decided. Reasons for choosing the medical profession were statistically significant according to age and gender (p = 0.001). Conclusion: The choice of medical education in Pakistan is still affected by stereotypes thoughts with typical eastern influences. Parental wish is a strong and prevailing factor, followed by to serve humanity. Lack of career counselling and guidelines results in the health industry losing many future doctors every year, as well as loss of potential resources for their training. Keywords: Factors, medical profession, gender, career choice